Pengaruh Orientasi Pelanggan, Orientasi Penjualan, Pengalaman, Dan Likeability Wiraniaga Terhadap Kepercayaan Pelanggan Pada Wiraniaga Asuransi Syariah Di Surabaya - M. Adi Surya Anwar; Ririn Tri Ratnasari (Universitas Airlangga, 2016)
This study aims to determine the effect of customer orientation, sales orientation, experience, and Likeability To Customer trust of Islamic Insurances salesperson in Surabaya. This study uses a quantitative approach. This study used a sample of 100 respondents. Characteristics of the population in this experiment is the Islamic insurance customers in Surabaya. As for analysis technique used is multiples regression.Results from the study show that customer orientation, sales orientation, experience, and Likeability salespeople have significant effect on customer trust. Other results showed that customer orientation, experience, and Likeability have positively effect to customer trust, whereas sales Orientation have negatively effect to customer trust in Surabaya.